Sustainable and responsible investment in Indonesia and Malaysia: an event study on SRI-KEHATI and FTSE4GBM Indices - Klara Petra Theodora Targanski; Werner R. Murhadi (Management Development Centre (MDC) Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2021)
The purpose of this research is to examine the effect of SRI index on abnormal return of added to and deleted stocks of two countries, Indonesia (SRI-KEHATI) and Malaysia (FTSE4GBM). The effect was examined using CAAR of the stock around index announcement. This research was conducted using event study methodology. The samples used in this research are all the stocks that were added to and deleted from SRI-KEHATI index on 2009-2018 announcements and FTSE4GBM index on 2014-2018 announcements. The result of hypothesis test shows that SRI index announcement has negative significant effect to the added stocks to SRI-KEHATI’s CAAR before announcement, after announcement and cumulative periods, to added stocks to FTSE4GBM’s before announcement and cumulative periods, and to deleted stocks from FTSE4GBM’s after announcement and cumulative periods. SRI index announcements has positive significant effect to the deleted stocks from SRI-KEHATI’s CAAR before announcement. Information on SRI index announcements has effects to the decisions made by investors. Indonesian investors reacted negatively toward added stocks but not choosing deleted stock either after announcements. Malaysian investors reacted negatively toward both added and deleted stocks, added stocks are perceived better even if positive CAAR are insignificant after announcements.